Biomolecular phase separation in tumorigenesis: from aberrant condensates to therapeutic vulnerabilities - Lan Hu; Zikun Huang; Zhaoyong Liu; Ying Zhang (Molecular Cancer)
Abstract Biomolecular phase separation has emerged as a fundamental mechanism governing intracellular spatial organization and functional compartmentalization, and is increasingly recognized as a critical factor in tumor initiation and progression. Through multivalent molecular interactions, biomolecular phase separation contributes to the formation of condensates that mediate the assembly of membraneless organelles, coordination of signaling pathways, and transcriptional programs. Under physiological conditions, condensation contributes to the maintenance of gene expression homeostasis, stress adaptation, and metabolic balance. In cancer cells, however, biomolecular condensates (BMCs) often exhibit aberrant behavior, accompanied by alterations in their structure, components, and regulatory mechanisms. Such perturbations may disrupt cellular homeostasis and influence key biological processes including gene regulation, signal transduction, metabolic reprogramming, and immune responses, thereby modulating various cancer hallmarks. Although the mechanistic understanding of BMCs remains incomplete, their intrinsic plasticity and environmental sensitivity make them attractive therapeutic targets for cancer treatment. This review provides a comprehensive overview of the regulatory factors and functional mechanisms of BMCs in cancer biology, with a particular focus on their involvement in diverse cancer hallmarks. This review further summarizes emerging therapeutic strategies targeting condensation, aiming to inspire novel treatment opportunities.